Abstract ID: 80 Charged particles grid and minibeam radiation therapy: Monte Carlo dosimetry evaluations. (October 2017) - González, Wilfredo; Guardiola, Consuelo; Peucelle, Cecile; Martínez-Rovira, Immaculada; Prezado, Yolanda
Abstract : The dose tolerances of normal tissues continue being the main limitation in radiotherapy. As a strategy to overcome it we propose to ally inherent physical advantages of protons and heavy ions (up to Fe) with the normal tissue preservation observed when irradiated with submillimetric spatially fractionated beams (minibeam radiation therapy, MBRT)[1, 2] . This would allow the use of higher and potentially curative doses in the treatment of radioresistant tumors. This was the motivation for the exploration of this new radiotherapy approach. In this presentation we will summarize the main dosimetric features of this promising strategy evaluated by Monte Carlo simulations (GATE/Geant4), including the influence of the projectile fragmentation on low dose areas. We also will report on the dose distributions in high-resolution computer tomography analysis used to guide the pre-clinical trials in proton MBRT. In addition, the results of our studies on the minimum beam size compatible with proton and heavier ions MBRT will be presented.